ANALYSIS OF MICROCREDIT IN ECUADOR'S SAVINGS AND CREDIT COOPERATIVES - Chafla Chucho, Jhonatan Raul; Guamán Toalombo, Jefferson Javier; Evas Atupaña, Segundo Fabián (mktDESCUBRE, 2020)
The present research, shows the behavior of the microcredit in the Savings and Credit Cooperatives of Ecuador, in the period 2014 - 2018, reflected in the analysis of the main variables that are related to this loan portfolio, to achieve the proposed, research It was carried out through the collection of data from authors of previous research, as well as the statistical reports of the Superintendence of Popular and Solidarity Economy, among other public and private entities, through a descriptive and analytical study, carried out with a research technique documentary type, to consider variables such as: participation against total portfolio, late payment, and interest rate. The microcredit in the institutions of this financial sector amounts to 3,715.40 million dollars with a default rate of 6.29%, at an interest rate that ranges from 22% to 28.50%. The placement of microcredit, by these financial entities, has been important in terms of their figures, however according to their social function, it has not become a major financial product within these financial entities, to achieve a socioeconomic impact cash.